2014
DOI: 10.3390/f5081967
|View full text |Cite
|
Sign up to set email alerts
|

Biomass and Carbon Stocks of Sofala Bay Mangrove Forests

Abstract: Mangroves could be key ecosystems in strategies addressing the mitigation of climate changes through carbon storage. However, little is known regarding the carbon stocks of these ecosystems, particularly below-ground. This study was carried out in the mangrove forests of Sofala Bay, Central Mozambique, with the aim of quantifying carbon stocks of live and dead plant and soil components. The methods followed the procedures developed by the Center for International Forestry Research (CIFOR) for mangrove forests.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
55
4
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(79 citation statements)
references
References 19 publications
(38 reference statements)
10
55
4
2
Order By: Relevance
“…However, there was no significant difference in tree components biomass estimation, with the exception of roots, among all the available allometric equations. In some cases the power function failed, and then transformed models were needed to develop significant allometric equations for different tree species, locations, and specific-components [7,25,27,28,[42][43][44][45][46][47].…”
Section: Discussionmentioning
confidence: 99%
“…However, there was no significant difference in tree components biomass estimation, with the exception of roots, among all the available allometric equations. In some cases the power function failed, and then transformed models were needed to develop significant allometric equations for different tree species, locations, and specific-components [7,25,27,28,[42][43][44][45][46][47].…”
Section: Discussionmentioning
confidence: 99%
“…A review by Komiyama et al (2008) identified 13 species-specific and two common (i.e., multi-species) models for prediction of aboveground biomass of mangroves, while nine speciesspecific models and one common model were identified for belowground biomass. Additional studies on mangroves that developed models for prediction of biomass not present in this review also exist (e.g., Kairo et al 2009;Kauffman and Donato 2012;Sitoe et al 2014). With the exception of the models developed by Kairo et al (2009) in Kenya and Sitoe et al (2014) in Mozambique, most of the models have been developed for mangroves in Asia.…”
Section: Introductionmentioning
confidence: 99%
“…ha -1 (Mandarin et al, 2016). This difference is thought to be caused by various factors, such as mangrove species composition, mangrove density, mangrove conservation level, and sediment conditions of mangrove habitat (Sitoe et al, 2014).…”
Section: Biomass Carbon Stock and Co2mentioning
confidence: 99%